EFEITO DE BIOESTIMULANTES VEGETAIS NO DESENVOLVIMENTO INICIAL DE PLANTAS DE SOJA - Ceolin, Sergio; Cavalcanti, Vittor; Moura, Daniel; Miranda, Hevelâyne; Santos, Ana Luiza; Graichen, Felipe (ANAIS DO ENIC, 2018)
-